Mining a Ubiquitous Time and Attendance Schema Using Random Forests for Intrusion Detection. (2016) - Promod, K.V.; Jacob, Binu
Abstract: Our case study used Random Forest to measure the intrusion of unauthorized personnel to certain designated areas of the organization. Intrusions happening at high security areas could cost the organization in terms of loss of material and in worst cases of lives as well. The time attendance system also act as a security system as it involves access to doors and barriers through which only authorized personnel should access.